Transcriptome analysis reveals the anticancer effects of fenbendazole on ovarian cancer: an in vitro and in vivo study - Xin Wang; Wenda Tian; Ning Wang; Xiangqun Yang; Zhenyan Liu; Lvzhou Li; Taoyu Zhao; Chuanlin Wang; Hongping Zhang; Hongying Yang; Yue Jia (BMC Cancer)
Abstract New treatment strategies for ovarian cancer, which is the deadliest female reproductive tract malignancy, are urgently needed. Here, we investigated the anticancer effects of fenbendazole (FBZ), a benzimidazole compound, on the regulation of apoptosis and mitotic catastrophe in A2780 and SKOV3 human epithelial ovarian cancer cells. Functional experiments, including Cell Counting Kit 8 (CCK-8), colony formation, and flow cytometry assays, were conducted to explore the effects of FBZ on the malignant biological behavior of A2780 and SKOV3 cells. RNA sequencing and western blotting were utilized to elucidate the underlying mechanisms by which FBZ affects cell apoptosis. We found that FBZ inhibited the proliferation and promoted the apoptosis of ovarian cancer cells in a dose-dependent manner. Furthermore, we reported the transcriptome profiling of FBZ-treated SKOV3 ovarian cancer cells. In all, 1747 differentially expressed genes (DEGs) were identified, including 944 downregulated and 803 upregulated genes. KEGG enrichment and Reactome enrichment analyses revealed that the DEGs were associated mainly with mitosis- and cell cycle-related pathways. Additionally, we found that FBZ may promote apoptosis via mitotic catastrophe. Finally, oral administration of FBZ inhibited tumor growth in a mouse model of xenograft ovarian cancer. Overall, these findings suggest that FBZ has therapeutic potential for the treatment of ovarian cancer.